THE APOSTOLIC DECREE AND OUR MEAT MENU: READING ACTS 15 IN REDEMPTIVE- HISTORICAL PERSPECTIVE - van Houwelingen, P.H.R. (Verbum Christi: Jurnal Teologi Reformed Injili, 2015)
The decision of the Jerusalem Council concerning Gentile believers - that they had to abstain, among other things, from meat with blood still in it and from sexual immorality - was officially recorded in order to be obeyed in the early Christian communities (Acts 15). It is echoed in Paul's letters, because this apostolic instruction was intended for non-Jewish believers like us. The prescription from Jerusalem was by no means incidental, it is rooted in basic principles of created life, and it was generally observed during the first centuries. Yet, most Christians today no longer feelbound bythis biblical rule and have no problem with eating blood pudding or rare steak. The purpose of this article is to explain why, in the course of time, the Apostolic Decree was considered to have become obsolete. In a church with an increasing number of Gentile Christians, the redemptive-historical necessity of the decree had ceased to exist.